Analysis of the Influence of Halal Certification on Improving the Performance and Profitability of SMEs in Surakarta - Purwanto, Purwanto; Cholis, Muhammad (Universitas KH. Abdul Chalim Mojokerto, 2026)
Halal certification is a strategic issue for the development of SMEs in Indonesia in increasing competitiveness and market access. This study analyzes the influence of halal certification on the performance and profitability of SMEs in the city of Surakarta. The mixed method approach was used by distributing questionnaires to 70 SMEs (42 halal-certified, 28 non-certified) and in-depth interviews with SMEs actors and sharia economists. Quantitative data were analyzed using correlation and regression tests, while qualitative data were analyzed by triangulation for validation of findings. The results showed a significant positive effect of halal certification on operational performance (r₁ = 0.687), marketing performance (r₂ = 0.732), and profitability (r₃ = 0.573) with p < 0.01. Halal certification improves performance through expanding institutional market access, premium pricing, and increasing consumer confidence. Qualitative findings confirm that halal certification serves as a quality signal and effective product differentiation. Implementation faces the challenges of high costs, procedural complexity, and limited human resources. The research recommends government subsidy programs, simplification of certification procedures, and the development of halal business clusters to optimize the impact of halal certification for Surakarta SMEs.